Analisis Risiko Pembiayaan Musyarakah pada Bank Syariah Indonesia KC Medan - Lamsina Harahap; Zainarti Zainarti (Jurnal Ekonomi Manajemen Perbankan, 2025)
Musyarakah financing at Bank Syariah Indonesia KC Medan is a partnership between the bank and customers in various economic sectors, where both parties share profits and losses based on an agreed proportion. Despite offering significant potential, this financing product also carries several risks that need to be addressed. The main risks associated with musyarakah financing include credit risk, market risk, and operational risk. Credit risk arises if customers fail to meet their obligations, potentially affecting the bank's stability. Market risk is related to fluctuations in the prices of goods or services that are part of the musyarakah, which can impact income and profits. Additionally, operational risk encompasses internal factors related to financing management and ineffective monitoring. To mitigate these risks, Bank Syariah Indonesia KC Medan needs to implement effective risk management, assess the feasibility of financing, and enhance transparency and oversight in every musyarakah transaction.